Legislative Policy on Compensation for Breach of Property Transfer (A Comparative Study) - Ali Sahib, Assist. Lect . Abbas (Basra studies journal, 2024)
Property ownership is a fundamental aspect of modern society and holds significant financial value for individuals due to its high monetary worth. This high value may deter property transfer by one of the contracting parties in transactions involving property transfer. This phenomenon was evident in Iraqi society during the 1970s, prompting legislative intervention to address it through a specific legislative policy distinct from other comparative legislations. This policy was based on several criteria and implemented within a specific scope of treatments.